Situation Report: Romania, 11 February 1969 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Ceausescu Again Rejects the Theory of "Limited Sovereignty" Czechoslovak Military Delegation to Romania Poliansky [Polianskii] Receives Romanian Charge d'Affaires Bodnaras' 65th Birthday Celebration Coverage of Italian Communist Party Congress Economic News